Incidencia de infecciones asociadas a la atención de salud en pacientes hospitalizados en la unidad de cuidados intensivos del Hospital Isidro Ayora de Loja. - Álvarez Figueroa, Leydi Magaly (2016)
The health-care associated infections (HAI) previously called nosocomial or in-hospital infections are the ones that a patient acquires while receiving treatment for any medical or surgical condition and in whom the infection had not been showcased or was in incubation period when checking-in at the health center. These infections are associated with several causes including but not limited to the use of medical devices, postsurgical complications, transmission among patients and healthcare workers, or as a result of frequent consumption of antibiotics. In addition, the HAI are caused by a variety of infectious agents, including bacteria, fungi and viruses. The HAI are considered as an adverse event resulting from health care that unintentionally produces some damage to the patient. This research work is intended to determine the incidence of health-care associated infections in hospitalized patients in the intensive care unit at Isidro Ayora General Hospital from Loja during the period June-November 2015 including the most frequent infection and germs. By using the scientific method and through data collected by means of a form for each patient, it was determined that the most frequent germ was Pseudomonas aeruginosa, followed very closely by Klebsiellapneumoniae and, the infection that was found more frequently was the ventilation-associated pneumonia. Keywords: infection, intensive care, germ.